2018
DOI: 10.1186/s12884-018-2036-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of community based advance distribution of misoprostol in Himachal Pradesh (India): lessons and way forward

Abstract: BackgroundPostpartum Hemorrhage remains the leading cause of maternal mortality. To prevent PPH, Misoprostol tablet in a dose of 600 micrograms is recommended for use immediately after childbirth in home deliveries wherein the use of oxytocin is difficult. The current article describes an implementation of “community based advance distribution of Misoprostol program” in India which aimed to design an operational framework for implementing this program.MethodsThe intervention was carried out in Janjheli block i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…points in Afghanistan [35], 39% points in Ghana [34], and 46% points in India [39] at the end of the intervention when compared to the baseline (Figure 2). A qualitative study among health professionals in Laos also indicated that community distribution of misoprostol, for the prevention of PPH, is acceptable to community members and stakeholders and it is a feasible interim solution until access to facility birth is improved.…”
Section: Diversion Of Facility Birthmentioning
confidence: 98%
See 2 more Smart Citations
“…points in Afghanistan [35], 39% points in Ghana [34], and 46% points in India [39] at the end of the intervention when compared to the baseline (Figure 2). A qualitative study among health professionals in Laos also indicated that community distribution of misoprostol, for the prevention of PPH, is acceptable to community members and stakeholders and it is a feasible interim solution until access to facility birth is improved.…”
Section: Diversion Of Facility Birthmentioning
confidence: 98%
“…Seven of the studies were from Africa and the remaining seven were from Asia. Three qualitative studies [33,25,12], seven observational studies [34][35][36][37][38][39][40], and four experimental or quasi-experimental studies [41][42][43][44] were included in this review. All studies were published from 2006 to 2018.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the studies were from Africa and the remaining seven were from Asia. Three qualitative studies [35,26,12], seven observational studies [36][37][38][39][40][41][42], and four experimental or quasi-experimental studies [43][44][45][46] were included in this review. All studies were published from 2006 to 2018.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Ten studies (five observational before-after studies, four experimental or quasi-experimental trials, and one qualitative study) reported on the impact on facility birth as the outcome [38,39,37,36,41,35,[43][44][45][46]. All five before-after household surveys reported increased facility delivery coverage after the intervention: four percentage points increase in Nepal [39] and Liberia [38], 11% points in Afghanistan [37], 39% points in Ghana [36], and 46% points in India [41] at the end of the intervention when compared to the baseline (Figure 2).…”
Section: Diversion Of Facility Birthmentioning
confidence: 99%